Can a university reproductive medicine centre be financed under the pre-existing general conditions in Germany? - Hildebrandt, Thomas; Oversohl, Nicola; Dittrich, Ralf; Lotz, Laura; Beckmann, Matthias; Lux, Michael P. (Geburtshilfe und Frauenheilkunde, 2019)
Background Reduced resources for financing healthcare services are available to the German health system. For this reason, demographic development represents one of the greatest challenges for the German health system. Reproductive medicine can offer potential solutions and counteract the ageing of the population through an increase in the birth rate. Most reproductive medical treatments take place in private centres. For the development of new, innovative therapeutic approaches, continuing education and scientific advancement, university centres are essential. Materials and Methods Using multistage contribution margin accounting, IVF and ICSI treatments at the University Fertility Centre Franken (UFF) were investigated in 2012. The cost situation from the perspective of the patient couple and the statutory payer were contrasted with the cost and revenue situation of the service provider as a university reproductive medicine centre. Results The costs for the patient couple for an IVF treatment cycle were 538.71 € and for an ICSI cycle, 700.07 €. For the payer, the costs, including the university flat rate (194.80 €) to be paid, amount to 733.51 € for an IVF cycle and 894.87 € for an ICSI cycle. The payments of the patient couple and the payer were added and this yielded total costs of 1272.22 € and 1594.94 €. The University Fertility Centre Franken, as a part of the Department of Gynaecology of the Erlangen University Hospital, incurred costs of 1364.47 € for an IVF treatment cycle and 1423.48 € for an ICSI treatment cycle. In addition, the OB/GYN clinic had to pay the university hospital a flat general expense rate of 14.9% of the income. There was thus a loss for the department of gynaecology of 281.81 € for an IVF cycle and 66.19 € for an ICSI cycle. Discussion From the perspective of a university reproductive medicine centre, IVF and ICSI treatments currently cannot be performed in a cost-covering manner. At the same time, a reproductive medicine treatment cycle represents a significant financial burden on the patient couple due to only partial cost coverage by most statutory health insurance funds. This therefore demonstrates a need for action in health policy to revise and, in the interest of the patient couples, reproductive medicine centres and, not least of all, in the interest of society, to improve existing cost absorption policies and thus also benefit from this as a society over the long term.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Continuing education; Endocrinology; Financial resources; ICSI; IVF; Reproductive medicine